2016
DOI: 10.5010/jpb.2016.43.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Simple sequence repeat marker development fromCodonopsis lanceolataand genetic relation analysis

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.Abstract In this study, we developed 15 novel polymorphic simple sequence repeat (SSR) markers by SSR-enriched genomic library construction from Codonopsis lanceolata.We obtained a total of 226 non-redundant con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…The mean PIC value of the SSR markers developed in the present study using wild ( G. lepidota and G. echinata ) and cultivated ( G. uralensis and G. glabra ) licorice accessions was 0.730, which is higher than that reported for other medicinal plants: 0.314 for Zingiber officinale (Pandotra et al, 2013), 0.57 for Codonopsis lanceolata (Kim et al, 2016), and 0.272 for Festuca arundinacea (Tehrani et al, 2009). These results showed that the SSR markers developed in the present study have a higher diversity than those developed for other species.…”
Section: Discussioncontrasting
confidence: 74%
“…The mean PIC value of the SSR markers developed in the present study using wild ( G. lepidota and G. echinata ) and cultivated ( G. uralensis and G. glabra ) licorice accessions was 0.730, which is higher than that reported for other medicinal plants: 0.314 for Zingiber officinale (Pandotra et al, 2013), 0.57 for Codonopsis lanceolata (Kim et al, 2016), and 0.272 for Festuca arundinacea (Tehrani et al, 2009). These results showed that the SSR markers developed in the present study have a higher diversity than those developed for other species.…”
Section: Discussioncontrasting
confidence: 74%
“…For the first time, ten microsatellite polymorphic loci were developed for C. pilosula, and the polymorphism of each locus was evaluated, using 27 individuals from four geographically distant populations of the 33 primers pairs, a total of 14 effectively amplified the target regions and 10 displayed polymorphic banding patterns (49). The PCR-based microsatellite amplification enables to create a distinctive pattern and a particular description for an individual, because of that it was used to identify and authenticate plants showing inter-specific variation (50).…”
Section: Microsatellitementioning
confidence: 99%
“…According to reports, it was indicated that C. pilosula transcriptome SSR is commonly used in China, as a total of 7327 SSRs were searched in the transcription group of C. pilosula, and by comparing the current frequency of C. pilosula SSR with other medicinal plants, C. pilosula frequency was lower than that of Salvia miltiorrhiza and higher than that of Ginseng (5). SSR markers were effectively identified and implemented to explore the genetic variation and the construction of the population in C. tangshen and C. pilosula (50). This technique was also used to study genomic variability in C. lanceolate (20).…”
Section: Simple Sequence Repeats Markers (Ssrs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The application of DNA molecular markers in studying the genetic variation in Codonopsis has been reported [ 11 ] and showed that Codonopsis species were difficult to classify and discriminate using conventional markers. Previous studies have used nuclear internal transcribed spacer (nrITS) [ 12 ], microsatellite polymorphic loci [ 13 ], simple sequence repeats (SSRs) [ 14 ], inter simple sequence repeats (ISSR), random amplified polymorphic DNA (RAPD) [ 15 ], amplified fragment length polymorphism (AFLP), sequencing-based markers (SNP) to discriminate Codonopsis species. In particular, Hwang et al used the genetic information from the plastomes of Codonopsis lanceolata and Platycodon grandiflorus for molecular marker development.…”
Section: Introductionmentioning
confidence: 99%